Library Resources for the Foreign Born College Student - Mood, Terry Ann. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
A brief essay on the difficulties faced by college students who have recently emigrated to the United States, introduces a suggested annotated list of general reference books and works on Africa, Asia, and the Middle East which college libraries can provide for the use of immigrant students. It is noted that immigration to the United States has been increasing, particularly from the Asian and African countries, and that immigrant students must deal with language problems and also must adjust to new educational methods and different types of library service. The list of library sources for students of foreign origin includes general encyclopedias, sources of international statistics, biographical dictionaries, sources of international business information, news directories, and periodical indexes covering international affairs. Also listed are encyclopedias, handbooks, yearbooks, dictionaries, atlases, sources of statistics, biographical sources, news summaries, bibliographies, and periodical indexes specific to Africa, Asia, and the Middle East. A total of 108 reference books are included. (ESR)
Media Staff.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Libraries; Annotated Bibliographies; College Students; Foreign Countries; Higher Education; Immigrants; Postsecondary Education; Reference Materials; Student Adjustment; Africa -- Asia; Middle East; Reference Materials, Bibliographies